IMPLEMENTASI KEBIJAKAN PROGRAM PEMBINAAN WARGA TRANSMIGRASI PADA UNIT PEMUKIMAN TRANSMIGRASI TINAUKA DI KABUPATEN DONGGALA - Muzakkir, Muzakkir (Katalogis, 2013)
This research aimed to analyze the implementation of the extension policy on economy, social and culture, and spiritual mentality of the transmigration villagers at the UPT of Tinauka, Donggala Regency. The theory used is George Edward III consisting of four variables: communication, resources, disposition, and structure of bureaucracy. This was qualitative research in which there were nine informants by employing purposive sampling. The techniques of data collection were observation, interview, and documentation. The data were analyzed qualitatively through these techniques: editing, classifying, interpreting, and drawing conclusion. In general, the implementation of the transmigration extension program policy has not run well. Of these four variables affecting the implementation policy, three variables: communication, resources, and structure of bureaucracy were not effective. It is found that 1) in communication variable, the personnel did not carry out regular extension because of incompetence in effective communication and low understanding of their responsibilities; 2) in resources variable, although the personnel have good facilities, they did not do their responsibilities because of low education (graduated from elementary school only), low incentive, and no training on UPT management 3) in disposition variable, the extension program ran well because the personnel have commitment and openness to the villagers by distributing the villagersâ€™ rights well, 4) in structure of bureaucracy variable, because of ineffective communication and low education qualification, the extension was carried out by the external personnel. This has made the standard operational procedures (SOP) not well-implemented.Â Â